A comparative study of general waste management practices in a campus of a medical university located in the purview of a municipal corporation of a South Indian state - Dondapati, Sujith Kumar S.; Ravikumar, Thanjavur S.; Guthi, Visweswara Rao; Ade, Anju D.; Deekala, Ravi Sankar; Kondagunta, Nagaraj (International Journal Of Community Medicine And Public Health, 2018)
Background: General waste is the waste that does not pose an immediate hazard or threat to health or to the environment. Waste management activities include collection, transportation, treatment and disposal of wastes. Academic institutions produce wastes, which are not disposed of effectively or economically. The result is littering and accumulation of garbage, which cause pollution. The objective of the current study is to examine and compare the general waste management practices of an university with current waste management rules in force. Methods: The current observational and comparative study was carried in an autonomous medical university located in South India. Waste is managed by Campus Maintenance Committee and Swachh Bharath committee under supportive supervision of Department of Community Medicine. The authors have observed the practices per se, talked with all the stakeholders of waste management in the institute, and presented their observations. The observations were compared with the standard practices of waste management to be adhered by academic institutions as per the rules of waste management. Results: Everyday 200-250 Kg of solid waste is generated in the university campus. General waste generated from different sources is grouped into black bags and sent to the dumpsite of campus. The corporation workers separate dry waste from wet waste and transport to the corporation dumpsite in separate blue and green drums separately. Conclusions: The steps taken by the university authorities like division of campus into areas with group leaders to facilitate ownership and accountability and formation of committees and regular meetings to facilitate coordination have shown results.